DETERMINATION AND VALIDATION OF MEBHYDROLINE NAPADISYLATE IN TABLETS BY HPLC - Lestyo Wulandari (Indonesian Journal of Chemistry, 2008)
An accurate and sensitive HPLC method has been developed for the determination of mebhydroline napadisylate in the tablet. The Chromatography was performed on a reversed phase C-18 column, using a mobile phase of acetonitrile : ammonia 25% (80 : 20 v/v) at ambient temperature 25±5 °C and UV detection operates at 320 nm in an overall analysis time of about 15 min, based on peak area. This HPLC method is selective, precise, and accurate and can be used for routine analysis of pharmaceutical preparation in industrial quality-control laboratories.